Hyperoche medusarum (KRØYER, 1838) (Amphipoda, Hyperiidae) and Mnemiopsis mccradyi (Mayer, 1910) (Ctenophora): a new host and first record of this association for the Southwestern Atlantic - Sorarrain, Dora (2001)
The association of gelatinous zooplankton (ctenophores, medusae, siphono- phores, and salps) with hyperiid amphipods, has reached a total of 85 species of amphipods up to 1980 (Harbison et al., 1977; Laval, 1980). Some of these amphipods begin their life cycle as obligate parasites, being found afterwards as free-swimming adults in the plankton (Von Westernhagen, 1976; Hoogenbaum & Hennen, 1985; Dittrich, 1992). Others use the host as a substrate, as food for their brood, and protection against enemies during their whole life. The amphipod Hyperoche medusarum (Krøyer, 1838), has been found as a parasite on six species of cnidarian medusae and ve ctenophores (Laval, 1980; Cahnon et al., 1986). The present study reports its association with Mnemiopsis mccradyi (Mayer, 1910) observed on live specimens captured during the austral summer of 2000 in the harbour of Mar del Plata, Argentina ( g. 1). Sixty-eight specimens of Amphipoda were found among the tissues, in cavities of the body, and over the surface of 24 ctenophores, with an average of 2-3 individuals per host. These observations were complemented aboard the RV “Canepa”, with fixed samples taken during December 1999 in coastal waters of the district of Buenos Aires, between 36º 30'S and 38º 30' S ( fig. 1). These specimens were identi ed on board, previous to their conservation with formalin.